Development of sustainable biopolymer-based composites for lightweight applications from agricultural waste biomass: A review - Phiri, Resego; Mavinkere Rangappa, Sanjay; Siengchin, Suchart; Oladijo, Oluseyi Philip; Dhakal, Hom Nath (Advanced industrial and engineering polymer research, 2023)
The exhaustion of available natural resources and rising concerns about the environment have prompted a growing desire to discover innovative ways to produce environmentally friendly materials. In an effort to alleviate environmental issues connected to the disposal of agricultural waste, many studies have engaged on research pertaining to agricultural waste management. Every year, there are enormous amounts of agro based waste created, which is a major issue from an economic and environmental standpoint. These wastes can be utilized as secondary raw materials to create value-added products in accordance with the circular economy's guiding principles. The exploitation of natural agricultural wastes has become critical for the development of sustainable biopolymer-based composites for lightweight applications. To this extent, this review presents an overview of the development and utilization of agricultural wastes to create biopolymers building blocks to be coupled with natural reinforcements for the fabrication of sustainable bio composites for lightweight applications. Common agricultural derived biopolymers are discussed. This review also highlights major bio composite fabrication methodologies and potential applications including challenges and opportunities in the development of sustainable biopolymer-based composites from agricultural waste biomass. It was concluded that the development of sustainable biopolymer-based composites from agricultural biomass offers a promising route towards a more environmentally friendly future.